2009
DOI: 10.1177/147323000903700103
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Indices and Functions Differentiating Patients with the β-Thalassaemia Trait from those with Iron Deficiency Anaemia

Abstract: This study examined the diagnostic accuracy of nine indices to discriminate between patients with mild-to-moderate (haemoglobin 8.5 -11 g/dl) or moderateto-severe (haemoglobin < 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 12 publications
6
21
0
Order By: Relevance
“…in their study proved S and L as the best discrimination index with highest YI. [28] Similarly, Yeo et al . reported a 38.7% increase in accuracy and 31.1% decrease in confirmatory testing among pregnant patients.…”
Section: Discussionmentioning
confidence: 98%
“…in their study proved S and L as the best discrimination index with highest YI. [28] Similarly, Yeo et al . reported a 38.7% increase in accuracy and 31.1% decrease in confirmatory testing among pregnant patients.…”
Section: Discussionmentioning
confidence: 98%
“…8 Keikhaei B et al, According to Youden's index (YI), Discriminating Functions in the order of highest to lowest were KI >G and KI > RDWI >E and FI >RBC>M I>EI >TI >SI >S and BI >RI>S and LI >B and FI. 12 Mussarrat et al, found RDWI is leading. 9 TP, SA et al Youden's index in decreasing order was as follows: RDW-SD > RBC COUNT> E and F >MI >RI >RDWI >G and K >SI >S and L >RDWCV.…”
Section: Discussionmentioning
confidence: 99%
“…7 Okan V et al studied the S and L and G and K indices were the best indicators in both comparisons and the RDW index was the worst. 12 Demir et al found the most accurate discriminative index for patients younger than 10 years was Shine and Lal and for those older than 10 years it was RDW index. 8 Keikhaei B et al, According to Youden's index (YI), Discriminating Functions in the order of highest to lowest were KI >G and KI > RDWI >E and FI >RBC>M I>EI >TI >SI >S and BI >RI>S and LI >B and FI.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who fulfilled the inclusion and the exclusion criteria were selected from the hematology out-patient clinic. Diagnosis of BTM was made in the case of hypochromic and microcytic hemoglobins, normal serum ferritin levels, and elevated serum levels of HbA2 (>4.0%) [26]. Hb electrophoresis was performed using Helena gel electrophoresis Beckmann densitometry.…”
Section: Study Populationmentioning
confidence: 99%